2005
DOI: 10.1634/stemcells.2005-0282
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Side Population of Cancer Cells from Human Gastrointestinal System

Abstract: STEM CELLS 2006;24:506 -513

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
439
1
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(463 citation statements)
references
References 30 publications
18
439
1
2
Order By: Relevance
“…CD133 þ HCC cells confer chemoresistance to conventional chemotherapeutic agents We hypothesized that CD133 þ HCC cells, which we have recently shown to represent the exclusive population of CSCs in HCC, would demonstrate resistance to traditional chemotherapeutic agents (Dean et al, 2005;Haraguchi et al, 2006). Both cell proliferation and apoptosis binding assays were used to examine the sensitivity of sorted CD133 þ and CD133 À cells from both human HCC cell line PLC8024 (Figure 1, expressed CD133 in 60% of the cells) and short-term culture of cells derived from CD133 þ (Huh7 human cell line)-induced xenograft tumor (Ma et al, 2007) (data not shown, expressed CD133 in 65% of the cells).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CD133 þ HCC cells confer chemoresistance to conventional chemotherapeutic agents We hypothesized that CD133 þ HCC cells, which we have recently shown to represent the exclusive population of CSCs in HCC, would demonstrate resistance to traditional chemotherapeutic agents (Dean et al, 2005;Haraguchi et al, 2006). Both cell proliferation and apoptosis binding assays were used to examine the sensitivity of sorted CD133 þ and CD133 À cells from both human HCC cell line PLC8024 (Figure 1, expressed CD133 in 60% of the cells) and short-term culture of cells derived from CD133 þ (Huh7 human cell line)-induced xenograft tumor (Ma et al, 2007) (data not shown, expressed CD133 in 65% of the cells).…”
Section: Resultsmentioning
confidence: 99%
“…To date, the existence of CSCs has been proven in the context of many cancers, including those of leukemia, breast cancer, glioblastoma, prostate cancer, pancreatic cancer and colon cancer (Lapidot et al, 1994;Bonnet and Dick, 1997;Al-Hajj et al, 2003;Hemmati et al, 2003;Singh et al, 2003Singh et al, , 2004Collins et al, 2005;Ponti et al, 2005;Haraguchi et al, 2006;Patrawala et al, 2006;Li et al, 2007;O'Brien et al, 2007;Ricci-Vitiani et al, 2007). Recently, we have determined that HCC is hierarchically organized and originates from a primitive stem/progenitor group of cells for which CD133 þ precursors constitute one of the most immature stage (Ma et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking the N and A1B1 domains of CEACAM5/CEACAM6 can impede the metastatic process (Blumenthal et al, 2005). Interestingly, another study showed that the CEACAM6 gene was one of the most overexpressed genes in a side population of cells of hepatocellular carcinoma (Haraguchi et al, 2006). Most of the side population of cells are considered to be equal to stem cells that show strong chemoresistance to anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Also in Bcrp1/Mdr1a/1b triple knockout mice, it was shown that Bcrp1, but not Mdr1a/1b, is responsible for the SP phenotype in the bone marrow, while both transporters are required for the SP phenotype in the mammary gland (Jonker et al, 2005). It has now been demonstrated that SP cells are present in several tumour samples, possess stem cell-like properties, overexpress BCRP and possess inherent drug resistance (Haraguchi et al, 2006). Consistently, BCRP overexpression was reported on primary CML CD34 þ cells (Jordanides et al, 2006).…”
Section: Bcrp In Stem Cellsmentioning
confidence: 99%